Experimental investigation on the effect of PCM and Nano-enhanced PCM of integrated solar collector performance - Saw, C.L. (WITPress, 2013)
The availability of hot water is essential for overnight industrial and domestic use. Integrating the solar heater with thermal energy storage showed a promising result on hot water production when sunlight is not present. In the present work, an outdoor experimental investigation of a flat plate solar collector was carried out with PCM and nano-enhanced PCM. The phase change material (PCM) used in this experiment is paraffin wax. However, 1 weight fraction of 20nm copper nanoparticles was added to improve the properties of the compound. Three cases have been investigated, namely, without PCM, with PCM and with nano-enhanced PCM (nano-PCM). It was found that at the operational mode of 0.5 kg/min and at a 10° inclination angle, with PCM and nano-PCM, hot water at 40.2°C and 40.8°C was produced the following morning. However, without the PCM case hot water was produced at 35.2°C. The system was enhanced by 6.9 and 8.4 respectively when PCM and nano-PCM were used. © 2013 WIT Press.